2006
DOI: 10.1159/000091728
|View full text |Cite
|
Sign up to set email alerts
|

Update of Alpha Fetoprotein Growth-Inhibitory Peptides as Biotherapeutic Agents for Tumor Growth and Metastasis

Abstract: The present update describes the biological activities of an alpha fetoprotein (AFP)-derived peptide termed the growth-inhibitory peptide (GIP), which is a synthetic 34-amino acid segment produced from the native molecule. The GIP has been shown to be growth-suppressive in both fetal and tumor cells but not in adult cells. Even though its mechanism of action has not been completely elucidated, GIP has been shown to engage in cellular events such as endocytosis, cellular aggregation, hemagglution, and cytoskele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…By contrast, both Uriel et al [101] and Arnon et al [4] showed that human AFP could actually bind estrogens. In either case, human AFP-derived peptides are able to display some anti-estrogenic activity [14,66,102]. These AFP-derived peptides are currently under investigation as potential agents for treating estrogen-dependent breast cancers and other tumors [13,66].…”
Section: Afp Protects the Developing Female Brain From Estrogensmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, both Uriel et al [101] and Arnon et al [4] showed that human AFP could actually bind estrogens. In either case, human AFP-derived peptides are able to display some anti-estrogenic activity [14,66,102]. These AFP-derived peptides are currently under investigation as potential agents for treating estrogen-dependent breast cancers and other tumors [13,66].…”
Section: Afp Protects the Developing Female Brain From Estrogensmentioning
confidence: 99%
“…In either case, human AFP-derived peptides are able to display some anti-estrogenic activity [14,66,102]. These AFP-derived peptides are currently under investigation as potential agents for treating estrogen-dependent breast cancers and other tumors [13,66]. Finally, it is not known if a protection from maternal estrogens is actually required since the reigning idea is that in humans, androgens, not estrogens, are the primary cause of brain masculinization (reviewed in [107]).…”
Section: Afp Protects the Developing Female Brain From Estrogensmentioning
confidence: 99%
“…Other sets of data involving AFP-derived peptides have been generated in vitro involving cancer cell adhesion, cell-to-cell interactions, cell spreading, motility, migration, and growth [32,33] . Regarding cancer cell proliferation, GIP was found to inhibit growth in multiple BC cell lines in vitro and to inhibit cell-tocell contact inhibition overgrowth in cultured MCF-7 cells [33][34][35] .…”
Section: Biological Activities Of Afp-derived Peptidesmentioning
confidence: 99%
“…The final involvement of GIP with cancer cell activities was demonstrated using in vivo models of human BC xenografts in mice. GIP was reported to suppress cancer growth/proliferation in both xenograft and homograft models of MCF-7, GI-101, MDA-MB-231, and 6WI-1 BC tumors in host mice [25,32] . In the human MDA-MB-231 BC in vivo mouse model, GIP injections resulted in a 3-fold reduction in BC metastasis to the lungs as compared to controls.…”
Section: Biological Activities Of Afp-derived Peptidesmentioning
confidence: 99%
“…AFP acts as a growth factor and biological response modifier, which affects cell proliferation (9)(10)(11)(12). AFP functions as a transporter of various ligands, such as steroid hormones and hemoglobin degradation products (bilirubin) (13)(14)(15). Ivanov et al (16,17) reported that peptides resulting from hemoglobin degradation products affect tumor cell proliferation.…”
Section: Introductionmentioning
confidence: 99%